Rancangan Bangun Media Pembelajaran Bintaro (Bianglala Pintar Trigonometri) Pada Materi Trigonometri Kelas X SMK Negeri 37 Jakarta Selatan - Nilam Sari Pailokol; Nabila Nabila; Nurma Tambunan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to produce intuitive, interesting, and efficient mathematics learning media. This research is a development research that uses research and development (r&d) with the addie model that covers a sequence of stages ranging from analysis, design, development, implementation, and evaluation. This study was conducted on students of x grade smk netherlands 37 south jakarta. The research subjects that used are students of class xi with bintaro learning media. The number of students in the class is 28 students. The data collection techniques that used are validation and questionnaire filling. The result of this study shows that the use of bintaro props can be used as an alternative to help students to understand mathematics lesson on trigonometric material.